A Surge in Cyber-Crime during COVID-19 - Muhammad Kashif; Aziz-Ur-Rehman; Muhammad Kashan Javed; Digvijay Pandey (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
The prime goal of this research is to investigate if the cyber-crime has risen during coronavirus. People are using more internet and electronic devices in this pandemic time in the purpose of to perform their works those are possible through internet, as they are unable to go out due to coronavirus. For collection of data, it has been generated a questionnaire comprising of six questions. In these restrictions’ times, data cannot be gathered interacting with people physically so social media has been used for gathering data. The questionnaire was sent to people through social media 1088 people were approached and 400 out of them responded on the questionnaire. The data is presented in different charts for analysis. This research is significant in knowing if people are being attacked or their data is being stolen more than ever before during coronavirus. The outcomes of this study show that people are literally suffering through a surge in cyber-crime and most of the people said their data have been stolen and they have also been attacked by hackers.